PENINGKATAN PENGETAHUAN DAN SIKAP MELALUI EDUKASI KEPUTIHAN DENGAN MEDIA AUDIOVISUAL PADA WANITA USIA PRODUKTIF - Lilis Fatmawati; A Maya Rupa Anjeli; Yuanita Syaiful; Alfina Bherlian Nada Ahmad (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2023)
Health education is a process of changing healthy behavior based on self-awareness, whether in individuals, groups or communities to maintain and improve health. One of the problems of women of reproductive age is the lack of knowledge about vaginal health. Most of the women of reproductive age in Sekapuk Village do not know the importance of keeping the vaginal area clean. This service aims to provide education through audiovisual to increase knowledge and change attitudes of women of reproductive age about vaginal discharge. This activity was carried out by the Nursing Science study program team, Faculty of Health Sciences, University of Gresik in collaboration with the Sekapuk Village which took place at the Sekapuk Village hall on 26-27 May 2023 with the method carried out, namely providing health education with audiovisual media, through this activity it is hoped that women aged Productive people are increasingly aware of the importance of keeping the vaginal area clean and preventing leucorrhoea, so that there is an increase in understanding and a change in attitude in preventing leucorrhoea. From this, the creation of educational media can be a lesson for women of reproductive age in preventing and anticipating that they do not experience vaginal discharge. The results obtained after the community service activities were an increase in knowledge and a change in attitude from negative to positive. Therefore, with education about vaginal discharge as an effort to increase public knowledge and awareness of the importance of preventing vaginal discharge to improve women's health status.